2011
DOI: 10.1299/jmmp.5.825
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Densification by Surface Rolling and Load Bearing Capacity of 1.5Cr-0.2Mo High Density Sintered Steel Rollers and Gears

Abstract: Surface rolling experiments and surface durability tests were carried out using powder metallurgy (P/M) gears made of 1.5Cr-0.2Mo single-press single-sinter (1P1S) high density (7.55×10 3 kg/m 3 ) sintered steel. The fundamental densification properties of this P/M material were first examined using P/M rollers. A high precision form rolling machine of two roller-dies transverse type was employed. The porosity became nearly zero from the surface down to a depth of at least 0.5 mm when the amount of decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In addition, surface rolling technology gives the very cost effective high precision processing of P/M gears with full surface density to improve the load bearing capacity. It has already been demonstrated that case-carburized P/M gears with a density above 7.5 Mg/m 3 made of 1.5Cr-0.2Mo pre-alloy sintered steel can achieve bending strength of 1.0 GPa 1,2) , which match with those of case-carburized gears made of the typical Cr-Mo wrought steel most commonly used for transmission gears. However, some serious problems occur as the density of the preform gear increases: the short die life and the damage of gear preforms in the compaction process, the heterogeneous void distribution in the gear teeth, the crack initiation at the tooth tip of surface-rolled gears, and so on.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, surface rolling technology gives the very cost effective high precision processing of P/M gears with full surface density to improve the load bearing capacity. It has already been demonstrated that case-carburized P/M gears with a density above 7.5 Mg/m 3 made of 1.5Cr-0.2Mo pre-alloy sintered steel can achieve bending strength of 1.0 GPa 1,2) , which match with those of case-carburized gears made of the typical Cr-Mo wrought steel most commonly used for transmission gears. However, some serious problems occur as the density of the preform gear increases: the short die life and the damage of gear preforms in the compaction process, the heterogeneous void distribution in the gear teeth, the crack initiation at the tooth tip of surface-rolled gears, and so on.…”
Section: Introductionmentioning
confidence: 94%
“…However, the inherent porosity in traditional single pressed and sintered products is one of the major factors causing reduction in the mechanical properties of PM parts [5,6]. Although new advances in powder metallurgy such as hot isostatic pressing (HIP), selective laser melting (SLM), and high-velocity compaction technology are used to manufacture high-performance components with homogeneous high density, the facilities required for these processes are more specialized and the production costs are higher compared with those of the surface rolling process [6][7][8]. Therefore, in order to expand the application field of PM parts, surface densification is a cost-effective and highly precise method enabling the surface of parts to be densified, while still keeping the internal porous state.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to expand the application field of PM parts, surface densification is a cost-effective and highly precise method enabling the surface of parts to be densified, while still keeping the internal porous state. Surface densification can greatly enhance the mechanical properties and surface properties of PM parts while retaining the advantages of powder metallurgy; specifically, maintaining the light weight and damping capacity of PM parts [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It has already been demonstrated that surface-rolled case-carburized gears with a density of greater than 7.5 Mg/m 3 made from this powder metallurgy (P/M) material can achieve bending and surface fatigue strengths of 1.0 GPa and 2.0 GPa, respectively [1][2]. However, because chromium can easily be oxidized during sintering or case-carburising in RX gas, there is a greater risk of reduction in the fatigue strength of the Cr-Mo P/M gears.…”
Section: Introductionmentioning
confidence: 99%
“…The reference gear GS and the counter pinion PS used in running tests were made from a wrought alloy steel (JIS SCM420), which corresponded to DIN25CrMo4. The surfacerolled P/M gears GK0R, GK1R, and GK2R were cut using a modified hob, as shown in Figure 2, to obtain a pronounced convex tooth profile around the pitch point, which was designed to obtain a true involute tooth profile after surface-rolling [2]. Other test gears were cut using the standard hob.…”
Section: Introductionmentioning
confidence: 99%